Manipulative Learning Media as an Effort to Improve Understanding of Tajweed Learning - Nur Sa’adah; Imam Tabroni; Yuanyuan Wang; Guijiao Zou (Yayasan Adra Karima Hubbi, 2023)
This class action research aims to improve students' understanding of tajweed learning through the application of manaipulative media in class IV MDTA Al-Mubarokah. The data needed in this study using Cycle I and II techniques. The results showed that the level of understanding of students towards learning tajweed through the application of manipulative media had reached 80% in cycle I and 90% in Cycle II. With the application of manipulative learning media, of course, to make it easier for students to be able to think in understanding the concept of tajweed learning conveyed by the teacher. Thus, teachers must be creative and innovative in learning, how teachers can create interesting and fun learning methods and media to motivate students to learn tajweed.